Penghitungan Jumlah Pinjaman pada Saat Koperasi Tidak Menghasilkan Keuntungan dengan Metode Persamaan Non-Linier Menggunakan Secant dan Implementasinya dengan MATLAB : Penghitungan Jumlah Pinjaman pada Saat Koperasi Tidak Menghasilkan Keuntungan dengan Metode Persamaan Non-Linier Menggunakan Secant dan Implementasinya dengan MATLAB - abdul, Abdul (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2023)
The profitability of cooperatives significantly impacts the amount of loans they possess. Therefore, it is crucial to calculate the minimum loan amount to maintain cooperative profitability. This study applies the iterative method of nonlinear equations using the Secant method, suitable for cases near the peak of graphs that cannot be computed using the Newton- Raphson method. The research sets a predefined iteration limit to control the number of iterations, enhancing overall calculation efficiency. The Secant method is implemented using MATLAB software, enabling precise analysis and evaluation of cooperative financial conditions. The research aims to provide practical guidance in cooperative financial management, focusing on maintaining profitability and loan growth. Thus, the study contributes not only theoretically to the field of nonlinear equations but also practically to cooperative management. Through this approach, the study seeks to deepen understanding of how cooperatives can utilize numerical methods to optimize their loan policies, avoid losses, and sustain financial viability. The findings serve as a foundation for researchers and practitioners to develop more  effective strategies in cooperative management, strengthening their role in supporting the local economy and empowering members sustainable.